Identification of key molecular biomarkers involved in reactive and neurodegenerative processes present in inherited congenital hydrocephalus - Ojeda-Pérez, Betsaida; Campos-Sandoval, José Ángel; García-Bonilla, María; Cárdenas García, Casimiro; Páez-González, Patricia; Jiménez-Lara, Antonio Jesús (BMC, 2021)
Periventricular extracellular oedema, myelin damage, inflammation, and glial reactions are common neuropathological events that occur in the brain in congenital hydrocephalus. The periventricular white matter is the most affected region. The present study aimed to identify altered molecular and cellular biomarkers in the neocortex that can function as potential therapeutic targets to both treat and evaluate recovery from these neurodegenerative conditions. The hyh mouse model of hereditary hydrocephalus was used for this purpose.
Keywords: Hidrocefalia; Marcadores bioquímicos; Biomarkers; Hereditary hydrocephalus; Energy dispersive X-ray spectroscopy (EDS); Lipids; Ultrahighperformance liquid chromatography-high-resolution mass spectrometry (UHPLC–HRMS); Matrix-assisted laser desorption ionization mass spectrometry imaging (MALDI-MSI); NG2 antigen; Oligodendrocyte progenitor cells; Proteomic